HUBUNGAN ANTARA SELF-REGULATED LEARNING, FUNGSI KOGNITIF, DAN TINGKAT STRES TERHADAP INTEGRITAS AKADEMIK MAHASISWA FK UPN "VETERAN" JAKARTA TAHUN 2023 - Fanshur Ahmad Zaki (2023)
Academic integrity violations are still common and tend to increase with the rise in publications on professionalism. This study aims to investigate the relationship between self-regulated learning, cognitive function, and stress levels on the academic integrity of medical students. The research was conducted using a quantitative analysis with a cross-sectional design involving 188 preclinical medical students from Faculty of Medicine in Jakarta. The sampling technique used was proportional stratified random sampling. Data were collected using previously validated instruments. Data analysis involved Chi-Square tests and Logistic Regression. The test results revealed that the majority of respondents had a sufficient level of academic integrity, a moderate level of self-regulated learning, an average cognitive test score of 50, and did not experience stress. There was a good relationship between slef-regulated learning, and stress scale towards academic integrity behavior. The Logistic Regression analysis results indicated that self-regulated learning, cognitive function, and stress levels have a significant relationship with academic integrity. These findings highlight self-regulated learning, cognitive function, and stress levels are importances in shaping academic integrity behavior. Further research is needed to identify additional factors that may influence academic integrity behavior in medical education. Keywords: Academic Integrity, Cognitive Functioning, Self-Regulated Learning, Stress Level.